Ley natural y ética discursiva. La ley natural en Tomás de Aquino como gramática del discurso moral (2009)
The present article is an attempt to make the Thomist ethics of the natural law intelligible to a supporter of Apel and Harbermas’s discourse ethics. In order to do so, it presents Aquinas’s theory of natural law as the moral discourse’s grammar. This ‘translation’ of Thomist ethics into contemporary terminology aims at establishing a dialogue with those who uphold discourse ethics by advancing the thesis that, Thomist ethics is superior to discourse ethics in performing the function of controlling the sense of propositions that belong to the moral discourse